POLA KEMITRAAN YAYASAN OBOR TANI (LSM) DAN MASYARAKAT DALAM MEMBERDAYAKAN PETANI DESA WONOKERTO KABUPATEN SEMARANG (PERIODE 2009-2013) - Erna Kurnia; Priyatno Harsasto (Journal of Politic and Government Studies, 2017)
The successfulness Obor Tani Foundation in empowering the farmer of Wonokerto Village Semarang Regency with the achievement Platinum GKMP award 2012 from the Ministry of walfare coordinator (Menteri Koordinator Bidang Kesejahteraan RI) is the background of this research. The issue of this research is: How is the partnership pattern involved between obor tani foundation and society in empowering Wonokerto society? How is the empowerment program held by the Obor Tani Foundation in attempt to increase the income of Wonokerto society? The purpose of this research is to describe how is the partnership pattern involved between Obor Tani Foundation and Wonokerto society incorporated in the Farmer Empowerment Center (Sentra Pemberdayaan Tani). Other, this research is aiming to explain how is empowerment process held by the obor tani foundation and wonokerto society in attempt to increase the income. To answer the issue and the purpose of this research, this research is using partnership theory and empowerment theory with qualitative method. Data collection technique is conducted by using interview and documentation. Data source triangulation technique is used in testing data validity and reliability. The result show that partnership involved between Obor Tani Foundation and society is mutualism partnership which the stakeholder involved get the advantage from the partnership. For society, the partnership held in 3,5 years give the impact of income increasing by the cultivation of dragon fruit, development of mini reservoir, and development of training home. Whereas for the obor tani foundation, the empowerment of Wonokerto village is a good performance so that increase the value of the foundation for the responsibility to PT Pertamina as a donor. Further Obor Tani foundation can collaborate the partnership with other big companies through CSR program. The successfulness of the high quality dragon fruit production also help the Hortimart Agro Center and other fruit shops in getting high quality of fruit stock without import. For the government, the empowerment program has an advantage in expanding the new jobs to reduce the poverty according to MDG’s 1st purpose. The recommendation of this research is the partnership model in empowering society held by obor tani foundation can be applicated to reduce the poverty in other village in Indonesia. Keywords: Partnership, empowerment, poverty reduction